PERAN ORGANISASI DAYAH DALAM PENGEMBANGAN SOFT SKILL KEPEMIMPINAN SANTRI: PERSPEKTIF GURU DAN PEMBINA ORGANISASI - Yunitawati Yunitawati; Juliana Juliana; Sry Wahyuni Rai; Rita Afrina; Pipit Sandriani; Iskandar Iskandar; Najmuddin Najmuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The development of leadership soft skills has become an important demand in 21st-century education because it plays a role in shaping individuals’ abilities in communication, decision-making, teamwork, responsibility, and initiative. In Islamic education, dayah organizations have strategic potential as a means of fostering students’ leadership through various organizational activities conducted continuously. However, studies examining the contribution of dayah organizations to the development of students’ leadership soft skills remain limited. This study aims to analyze the role of dayah organizations in developing students’ leadership soft skills based on the perspectives of teachers and organizational mentors. The study employed a qualitative approach with a descriptive design. The research informants consisted of three teachers who were directly involved in guiding dayah organizations and were selected using purposive sampling techniques. Data were collected through semi-structured interviews and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results showed that dayah organizations positively contribute to the development of students’ communication skills, decision-making abilities, teamwork, responsibility, and initiative. Activities such as student organization management, event committees, dormitory management, and muhadharah serve as effective means of developing leadership soft skills. The findings confirm that dayah organizations function as leadership laboratories that enable students to develop leadership competencies through direct experiences and social interactions based on Islamic values. Optimizing student organizations is necessary as an integral part of dayah education to prepare a generation that is characterized, adaptive, and competent. ABSTRAK Pengembangan soft skill kepemimpinan menjadi tuntutan penting dalam pendidikan abad ke-21 karena berperan dalam membentuk kemampuan komunikasi, pengambilan keputusan, kerja sama, tanggung jawab, dan inisiatif individu. Dalam pendidikan Islam, organisasi dayah memiliki potensi strategis sebagai sarana pembinaan kepemimpinan santri melalui berbagai aktivitas organisasi yang berlangsung secara berkelanjutan. Namun, kajian mengenai kontribusi organisasi dayah terhadap pengembangan soft skill kepemimpinan santri masih terbatas. Penelitian ini bertujuan menganalisis peran organisasi dayah dalam mengembangkan soft skill kepemimpinan santri berdasarkan perspektif guru dan pembina organisasi. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif. Informan penelitian terdiri atas tiga guru yang terlibat langsung dalam pembinaan organisasi dayah dan dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara semi-terstruktur dan dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa organisasi dayah berkontribusi positif terhadap pengembangan kemampuan komunikasi, pengambilan keputusan, kerja sama tim, tanggung jawab, dan inisiatif santri. Aktivitas seperti kepengurusan organisasi santri, kepanitiaan kegiatan, pengelolaan asrama, dan muhadharah menjadi sarana efektif dalam membentuk soft skill kepemimpinan. Temuan ini menegaskan bahwa organisasi dayah berfungsi sebagai laboratorium kepemimpinan yang memungkinkan santri mengembangkan kompetensi kepemimpinan melalui pengalaman langsung dan interaksi sosial berbasis nilai-nilai Islam. Optimalisasi organisasi santri diperlukan sebagai bagian integral pendidikan dayah dalam mempersiapkan generasi yang berkarakter, adaptif, dan kompeten.